(untitled) (Revista Internacional de Folkcomunicação, 2018)
This study objected to analyze the role developed by folk-activists in Padre Hildon Bandeira “rural urban” community, located in João Pessoa-PB, under the Local Development perspective and the Folkcommunication Theory. From the research was verified on witch circunstances the social actors contribute to the development of civic networks and communication, creating opportunities, socially democratizing the community and establishing relations of solidarity and trust, as well as raising social benefits with public authorities. Folk-activism; Communication; Citizenship; Local Development.